2021
DOI: 10.21873/cgp.20284
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches on High Throughput NGS Data to Unveil Mechanisms of Function in Biology and Disease

Abstract: In this review, the fundamental basis of machine learning (ML) and data mining (DM) are summarized together with the techniques for distilling knowledge from state-of-theart omics experiments. This includes an introduction to the basic mathematical principles of unsupervised/supervised learning methods, dimensionality reduction techniques, deep neural networks architectures and the applications of these in bioinformatics. Several case studies under evaluation mainly involve next generation sequencing (NGS) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the current study, RNA-seq, bioinformatics analysis, and RT-qPCR validation were conducted, which might provide a comprehensive view of the potential molecular mechanism engaged in the regulation of HCC cell malignant functions by HCC-MSC-derived exosomes ( 39 ). The data revealed that 217 upregulated and 162 downregulated DEGs were closely related to the regulation of HCC cellular functions by HCC-MSC-derived exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, RNA-seq, bioinformatics analysis, and RT-qPCR validation were conducted, which might provide a comprehensive view of the potential molecular mechanism engaged in the regulation of HCC cell malignant functions by HCC-MSC-derived exosomes ( 39 ). The data revealed that 217 upregulated and 162 downregulated DEGs were closely related to the regulation of HCC cellular functions by HCC-MSC-derived exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches are currently widely exploited for identification of image-based biomarkers using radiomics- 115,116 or digital pathology-based approaches. 117,118 Likewise, the use of machine learning applications for investigating fundamental biological processes has been described 119 and may therefore also provide a powerful tool for deconvoluting highdimensional genomic or proteomic data aimed at biomarker discovery. Datasets that are large enough and sufficiently clinically annotated for this purpose are, however, currently limited.…”
Section: Opportunities and Challenges For Precision Io Researchmentioning
confidence: 99%
“…But, Candida colonization is an important prerequisite for the occurrence of invasive candidiasis. For this reason, it is necessary to combine clinical manifestations and laboratory examinations to make a conclusion to guide the treatment (22,23). Compared with the huge amount of medical costs, targeted medication can significantly reduce the cost of treatment through defining the etiology using mNGS.…”
Section: Discussionmentioning
confidence: 99%